2019
DOI: 10.3892/ol.2019.10231
|View full text |Cite
|
Sign up to set email alerts
|

Screening of key miRNAs and evaluation of their diagnostic and prognostic values in nasopharyngeal carcinoma

Abstract: Increasing evidence has revealed the importance of microRNA (miRNA/miR) in cancer genesis and progression. The aim of the current study was to identify the key miRNAs involved in the onset and development of nasopharyngeal carcinoma (NPC) and to further evaluate their diagnostic and prognostic values. Microarray data were obtained and analyzed to screen differentially expressed miRNAs (DEMs) between patients with NPC and healthy controls. The target genes of the DEMs were predicted and their possible functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Narrowly, an existed study has pronounced that upregulated miR-18a promotes NPC cell progression via mediation of DICER1 [6]. In addition, it is noticed that overexpressed miR-18a in NPC is believed to connect with NPC metastasis and repressed miR-18a partially contributes to better prognosis of NPC patients [31]. Lately, it is surveyed that downregulation of miR-18a is capable of discouraging NPC proliferation, invasion, and migration [4].…”
Section: Discussionmentioning
confidence: 99%
“…Narrowly, an existed study has pronounced that upregulated miR-18a promotes NPC cell progression via mediation of DICER1 [6]. In addition, it is noticed that overexpressed miR-18a in NPC is believed to connect with NPC metastasis and repressed miR-18a partially contributes to better prognosis of NPC patients [31]. Lately, it is surveyed that downregulation of miR-18a is capable of discouraging NPC proliferation, invasion, and migration [4].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that as a member of the miR-17-92 cluster, the occurrence and development of tumors are tightly correlated with miR-18a. MiR-18a is related to tumor metastasis in nasopharyngeal carcinoma [24], astroglioma [25], breast cancer [26] and other tumor cells. The role of miR-18a in the pathogenesis of disease remains a challenging topic.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of NPC is high in Asia [16]. RT for various malignant tumors is an effective, standard therapeutic intervention that is commonly used.…”
Section: Discussionmentioning
confidence: 99%